Corpus Linguistics and Linguistic Theory (De Gruyter Mouton, 2005)
Corpus Linguistics and Linguistic Theory publishes high-quality, corpus-based research focusing on theoretically-relevant issues in all core areas of linguistic research (phonology, morphology, syntax, semantics, pragmatics) and other recognized topic areas. The journal features articles from a corpus-based approach that develop new methods, evaluate theoretical claims and offer analyses of linguistic phenomena within a theoretical framework.